Partial re-designing of the quantum information course: Adapting to advances in the field - Kumar Das, Sumanta (Improving University Science Teaching and Learning, 2023)
The Quantum Information course offered to the masters and PhD students at the Niels Bohr institute until 2016, was designed approximately ten years back. It was created to educate students in the basics of quantum information sciences. The course covers a wide variety of topics with a good balance between theoretical concepts and applications. However, over the past decade the field of quantum information have advanced substantially, and has become quite interdisciplinary. Furthermore, newer physical systems and technology has been developed to implement information processing at atomic levels. As such updating the course with some of the latest material and concepts is warranted. It is also necessary, to maintain the quality of the course at a standard, comparable to that offered in other top universities in Europe and North America. As such, in addition to including new material one needs to also re-define the intended learning outcomes (ILOs) of the course, which are even, not well aligned to the present version of the course.